DISCOURSE ANALYSIS OF SOCIAL COGNITION ON ELEMENTS OF KNOWLEDGE IN THE NOVEL OF ORDINARY PEOPLE TEUN A. VAN DIJK'S THEORY - Filia Dwi Lestari; Hasan Suaedi; Astri Widyaruli Anggraeni (Indonesian language and literature education program Majapahit Islamic University, 2025)
This research article discusses social cognition discourse in the element of knowledge in Andrea Hirata's novel The Ordinary People. Critical discourse analysis is an effort made to explain a text that occurs in a social phenomenon that is useful to know the interests within it. Social cognition is an important element in the process of forming views in a discourse that occurs within society. Especially in the element of knowledge that discusses factual beliefs shared by groups or cultures, with this the author will express his discourse based on knowledge gained from personal or group experience. This study aims to describe social cognition, especially the element of knowledge in the main character in the novel